2022
DOI: 10.1021/jacs.2c09477
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Elucidation of Solid and Solution Manganese Environments via Multiphase Operando Extended X-ray Absorption Fine Structure Spectroscopy in Aqueous Zn/MnO2 Batteries

Abstract: Aqueous Zn/MnO2 batteries (AZMOB) with mildly acidic electrolytes hold promise as potential green grid-level energy storage solutions for clean power generation. Mechanistic understanding is critical to advance capacity retention needed by the application but is complex due to the evolution of the cathode solid phases and the presence of dissolved manganese in the electrolyte due to a dissolution–deposition redox process. This work introduces operando multiphase extended X-ray absorption fine structure (EXAFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…The b values for the oxidation (peaks 1, 2) and reduction (peaks 3, 4) are calculated to be 0.87, 0.95, 0.87, and 0.88, respectively (Figure b). These results suggested that the charge storage behavior in the P-60-120 °C electrode is controlled by a hybrid mechanism of ion diffusion process and surface capacitive response . Moreover, the reversible capacity contributions of the P-60-120 °C electrode at different scanning rates could be quantitatively evaluated based on the eq , , i = k 1 v + k 2 v 1 / 2 where k 1 and k 2 are constants at specific scanning rates.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The b values for the oxidation (peaks 1, 2) and reduction (peaks 3, 4) are calculated to be 0.87, 0.95, 0.87, and 0.88, respectively (Figure b). These results suggested that the charge storage behavior in the P-60-120 °C electrode is controlled by a hybrid mechanism of ion diffusion process and surface capacitive response . Moreover, the reversible capacity contributions of the P-60-120 °C electrode at different scanning rates could be quantitatively evaluated based on the eq , , i = k 1 v + k 2 v 1 / 2 where k 1 and k 2 are constants at specific scanning rates.…”
Section: Resultsmentioning
confidence: 94%
“…These results suggested that the charge storage behavior in the P-60-120 °C electrode is controlled by a hybrid mechanism of ion diffusion process and surface capacitive response. 21 Moreover, the reversible capacity contributions of the P-60-120 °C electrode at different scanning rates could be quantitatively evaluated based on the eq 2, 40,47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a provides a classical example of σ-MnO 2 tunnels, where Zn 2+ is stripped out from a Zn metal anode during the discharging process and travels to intercalate into the layered structure in the charging process. Another cointercalation mechanism for the system with a special cathode has also been reported in recent publications, where Zn 2+ cointercalates with H + or H 2 O and is embedded in the cathode substrate in the form of hydrate or hydroxide . In general, the cathode in ZIBs based on the intercalation mechanism has an open structure: i.e., a specially designed ion storage host and layered ion transportation tunnel that allows facile insertion of Zn ions (eq ).…”
Section: Fundamentals and Mechanisms Of Zn-based Batteriesmentioning
confidence: 85%
“…Another cointercalation mechanism for the system with a special cathode has also been reported in recent publications, where Zn 2+ cointercalates with H + or H 2 O and is embedded in the cathode substrate in the form of hydrate or hydroxide. 103 In general, the cathode in ZIBs based on the intercalation mechanism has an open structure: i.e., a specially designed ion storage host and layered ion transportation tunnel that allows facile insertion of Zn ions (eq 2).…”
Section: Intercalation Mechanism Of Zibsmentioning
confidence: 99%